2020
DOI: 10.1002/jsfa.10658
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of mango cv. ‘Ataulfo’ peel and pulp against oxidative stress in streptozotocin‐induced diabetic rats

Abstract: BACKGROUND: Oxidative stress has been implicated in the pathogenesis and progression of diabetes mellitus. Both can damage the brain. Mango and its by-products are sources of bioactive compounds with antioxidant properties. We hypothesized that mango cv. 'Ataulfo' peel and pulp mitigate oxidative stress in the brain of streptozotocin-induced diabetic rats. RESULTS: Twenty-four male Wistar rats were divided into four groups: control, untreated diabetic (UD), diabetic treated with a mango-supplemented diet (MTD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…All animals consumed approximately 22–30 g/d, similar amounts to those previously reported for adult male Wistar rats, which, according to the experimental diets used, are equivalent to 63.58 ± 0.75 to 86.7 ± 0.54 kcal/d (Della‐Zuana et al., 2002). This energy intake has been previously reported by different authors, where male Wistar rats aged 12–14 weeks consumed an average of 78.4 kcal/day (Cázares‐Camacho et al., 2021). It is apparent that animals fed non‐supplemented diets consumed similar amounts and with minimal fluctuations throughout the experimental period, which suggests that caloric intake was unaffected by macronutrient composition of the diets.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…All animals consumed approximately 22–30 g/d, similar amounts to those previously reported for adult male Wistar rats, which, according to the experimental diets used, are equivalent to 63.58 ± 0.75 to 86.7 ± 0.54 kcal/d (Della‐Zuana et al., 2002). This energy intake has been previously reported by different authors, where male Wistar rats aged 12–14 weeks consumed an average of 78.4 kcal/day (Cázares‐Camacho et al., 2021). It is apparent that animals fed non‐supplemented diets consumed similar amounts and with minimal fluctuations throughout the experimental period, which suggests that caloric intake was unaffected by macronutrient composition of the diets.…”
Section: Resultssupporting
confidence: 83%
“…Table 2 shows the animals’ glycemia at the initial (week 0) and final (week 8) experimental week. Glucose levels at both sampling times were normal for male Wistar rats of similar age (Cázares‐Camacho et al., 2021), and did not vary in response to dietary composition or due to the PE treatment. This suggests that neither the HFD nor the PE treatment‐induced any significant changes to carbohydrate metabolism that were apparent on fasting glycemia.…”
Section: Resultsmentioning
confidence: 89%
“…These compounds, apart from their biological activity, stand out for their ubiquity in plants. Their presence in all kinds of fruits, vegetables and plant material has been extensively reported [ 74 , 75 ]. Over the last few years, by-products such as seeds, peels and leaves are gaining attention for their content of bioactive compounds, which is sometimes higher than in the edible parts [ 76 ].…”
Section: Phenolic Compounds From Fruit and Vegetable By-products: Neu...mentioning
confidence: 99%
“…Therefore, flavonoid-enriched extracts could show significantly high antioxidant levels, as several studies confirm, either by promoting endogenous antioxidants or scavenging free radicals [ 75 , 83 , 87 ]. For example, Duangjan et al (2021) reported that grape leaf extract promoted the gene expression of different cellular antioxidant enzymes such as CAT, SOD, GST and GPX in vivo [ 87 ].…”
Section: Phenolic Compounds From Fruit and Vegetable By-products: Neu...mentioning
confidence: 99%
“…Mangifera indica L. fruit is rich in bioactive phytochemical compounds with antioxidant properties including mangiferin that potentially exerts potent neuroprotective properties against diabetes mellitus-induced oxidative stress. (Cázares-Camacho et al, 2021) investigated effects of Mangifera indica L. supplemented diet (peel and pulp) on oxidative stress markers in two brain regions (cerebral cortex and cerebellum) of the STZ-induced diabetic rats and observed a decrease in lipid peroxidation in diabetic rats supplemented with Mangifera indica L. diet. In addition, the mango supplemented diet reduced polyphagia and weight loss, and maintained a stable glycemia in diabetic rats.…”
Section: Mangifera Indica Lmentioning
confidence: 99%